2007
DOI: 10.1002/micr.20374
|View full text |Cite
|
Sign up to set email alerts
|

Distal radial and ulnar arteries perforator‐based adipofascial flaps for covering hand traumatic defects

Abstract: The described fascial flaps offer several advantages over other local flaps, and are rather easy to perform and cover effectively both dorsal and palmar hand defects without causing significant functional deficits to the upper limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…44 Perforators from the distal cluster have also been described. 7,[31][32][33][34][35][36][37][38][39][40][41][42][43]45,46 It is demonstrated here that a large-caliber perforator was found to be present within 2 cm of the radial styloid in all of the 26 cadaver forearms dissected. In 100 percent of the specimens studied, there was a major, clinically relevant (Ͼ0.5 mm) cutaneous perforator from the radial artery found within this region.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…44 Perforators from the distal cluster have also been described. 7,[31][32][33][34][35][36][37][38][39][40][41][42][43]45,46 It is demonstrated here that a large-caliber perforator was found to be present within 2 cm of the radial styloid in all of the 26 cadaver forearms dissected. In 100 percent of the specimens studied, there was a major, clinically relevant (Ͼ0.5 mm) cutaneous perforator from the radial artery found within this region.…”
Section: Discussionmentioning
confidence: 90%
“…Many surgeons have reported use of perforator flaps from the forearm with good outcomes. 7,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Unfortunately, the location of the dominant perforator is difficult to determine using a handheld Doppler probe because of the superficial location of the radial artery. An anatomical study demonstrating the vascular territory and location of the most dominant perforators along the radial artery axis therefore becomes crucial to facilitate safer harvest and design of the radial forearm pedicle perforator flap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Koshima et al(1995) reported similar flaps based on the radial artery perforator alone, radial artery perforator flaps have been gradually adopted for reconstructing defects of the hand (Al Hoqail, 2009;Ignatiadis et al, 2007;Koshima et al, 1995;Medalie, 2002;Saint-Cyr et al, 2010). However, there is no definite description about the safe territory of the radial artery perforator-based flap.…”
mentioning
confidence: 99%
“…The latest discovery is the already well-known perforator flaps 1,2 used as free microsurgical transfers 1,[3][4][5] and also as local or regional flaps. [6][7][8][9][10][11][12][13][14][15] Local or regional perforator flaps represent an important resource in covering tissue defects in the forearm and the hand, but also allows the realization of the imperative needs of such a procedure 14 : to replace the tissues with similar ones; to minimize donor site morbidity, especially not to sacrifice a main vascular pedicle; to shorten the evolution and the recovery period.…”
mentioning
confidence: 99%